Visit Intention: Impact of Familiarity and Destination Image in The Bangka Belitung Islands - Nanang Wahyudin; Echo Perdana Kusuma; Ibrahim Ibrahim (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The digital transformation of tourism has redefined how familiarity with destinations is constructed, blending experiential encounters with vast informational exposure. Understanding how these distinct sources of familiarity influence cognitive and affective image formation and subsequently visit intention is crucial, particularly for emerging island destinations characterized by limited global recognition and perceived risk factors.Purpose: This study aims to: (1) develop and validate a multidimensional framework distinguishing experiential and informational familiarity, (2) examine the differential impacts of cognitive versus affective destination image components on visit intention, and (3) establish an integrated familiarity–image–intention model tailored to emerging island destinations, with Bangka Belitung, Indonesia, serving as the empirical context.Design/methodology/approach: Employing a rigorous quantitative methodology, we conducted a comprehensive online survey with 544 domestic travelers. Measurement instruments for familiarity and affective image evaluation were carefully designed and adapted from seminal works. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Reliability tests, convergent validity, and discriminant validity assessments were applied to ensure robust psychometric properties.Findings: The results reveal that both experiential and informational familiarity significantly influence cognitive and affective destination images, with affective image exerting a stronger predictive effect on visit intention. A direct positive relationship between familiarity and visit intention was also identified, independent of the mediating role of destination image. These findings support the Stimulus-Organism-Response (S-O-R) model, positioning familiarity as the stimulus, destination image as the organismic response, and visit intention as the behavioral outcome.Conclusion: This research demonstrates that affective destination image serves as a crucial mediator between familiarity and visit intention, particularly for island destinations. The findings provide both a theoretical framework for understanding tourist psychology and actionable insights for destination marketing organizations seeking to enhance visitation through targeted image management strategies.Originality/value: The study contributes by: (1) integrating dual familiarity types with dual image dimensions, (2) providing empirical evidence from understudied island contexts, and (3) resolving theoretical ambiguities concerning the relative importance of image pathways. Keywords: familiarity, destination image, visit intention, Island Tourism, Bangka Belitung